2023
DOI: 10.2147/idr.s398126
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss in Patients with Long-COVID-19: Objective and Behavioral Audiometric Findings

Abstract: Introduction The symptoms of COVID-19 are primarily respiratory system disorders. Sensorineural hearing loss can be caused by COVID-19, as other symptoms in the nervous system. Hearing loss may also be the only symptom or complication of this disease or the symptoms of long COVID-19. The study aimed to assess hearing in patients after COVID-19 infection. Material and Methods The study conducted ENT and full hearing assessment in COVID-19 infection. All patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The potential effect of COVID-19 infection on hearing loss adds another layer of complexity. There are reports of general hearing loss related to COVID-19 [37] as well as of certain other problems-for example, one preliminary report describes a higher incidence of Meniere's disease during the COVID-19 pandemic [38]. At the same time, it is well known that hearing loss may lead to tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…The potential effect of COVID-19 infection on hearing loss adds another layer of complexity. There are reports of general hearing loss related to COVID-19 [37] as well as of certain other problems-for example, one preliminary report describes a higher incidence of Meniere's disease during the COVID-19 pandemic [38]. At the same time, it is well known that hearing loss may lead to tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…In an online survey of over 3700 people, 5.2–6.4% reported hearing loss between months 4–7 after COVID-19 infection [ 71 ]. How SARS-CoV-2 affects the auditory pathway is not fully elucidated, but hearing problems may result from epithelial damage and vascular issues, such as microthrombosis [ 220 , 221 , 222 ].…”
Section: Symptoms Of Long Covidmentioning
confidence: 99%
“…Poor concentration, slowed thinking, difficulty paying attention, and focusing [181][182][183] Hyposmia/parosmia Partial or total loss of sense of smell/misperceiving odors (often pleasant odors seem unpleasant) [202,[206][207][208]210,212] Hypogeusia/dysgeusia Partial or total loss of sense of taste/altered perception of taste [202,[206][207][208]211,213] Hearing problems Hearing loss, tinnitus [76,[218][219][220]222] Ocular symptoms…”
Section: Brain Fogmentioning
confidence: 99%
“…1,2 While the etiology of hearing loss due to viral infections varies by virus, it has been suggested that COVID-19 may cause inflammation of nervous tissue and affect both the inner ear and auditory pathways. 3 The link between SNHL and COVID-19 was first reported in April 2020, in a COVID-19 patient with coincident SNHL. 4 Since then, there have been other reports on the association between SNHL and COVID-19 infection.…”
Section: Introductionmentioning
confidence: 97%